Factors associated with antidepressant responses to repetitive transcranial magnetic stimulation in antidepressant-resistant depression - Li, Cheng-Ta; Su, Tung-Ping; Cheng, Chih-Ming; Chen, Mu-Hong; Bai, Ya-Mei; Tsai, Shih-Jen (Frontiers in Neuroscience, 2022)
Background: A significant proportion of patients with major depressive disorder (MDD) failed to respond to antidepressant medications. Repetitive transcranial magnetic stimulation (rTMS) is an effective option for treating such treatment-resistant patients with MDD (TRD). Reliable clinical predictors for antidepressant responses to rTMS remain elusive. Methods: In total, 212 patients with MDD who failed to respond to at least one adequate antidepressant trial and had a detailed evaluation before rTMS were recruited for chart review. Demographic data, clinical characteristics, psychiatric comorbidities, symptom ratings [(e.g., objective and subjective depression, life stress, depression refractoriness by Maudsley Staging Method (MSM)], and antidepressant treatment responses were analyzed. Results: MSM-subitem1 (duration of current depressive episode; Beta = 0.209, p = 0.004), MSM-subitem5 (a history of ECT treatment; Beta = −0.210, p = 0.004), and psychiatric admissions (Beta = 0.241, p = 0.001) predicted antidepressant response of rTMS treatment. ECT was underutilized (only 3.3%). Psychiatric admissions [Exp(B)=1.382, p=0.021], a comorbidity of OCD [0.047, 0.005], and life stress level [0.984, 0.029] predicted the history of ECT treatment. Conclusion: Several clinical variables (e.g., number of psychiatric admissions, OCD as a comorbidity, and life stress level) were reliable clinical factors associated with antidepressant responses of rTMS treatment and may be utilized in combination with MSM subitems to evaluate levels of TRD. Key words: treatment-resistant depression, Maudsley Staging Method, psychiatric admissions, repetitive transcranial magnetic stimulation, responses